2013
DOI: 10.1038/nature12651
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for the modular recognition of single-stranded RNA by PPR proteins

Abstract: Pentatricopeptide repeat (PPR) proteins represent a large family of sequence-specific RNA-binding proteins that are involved in multiple aspects of RNA metabolism. PPR proteins, which are found in exceptionally large numbers in the mitochondria and chloroplasts of terrestrial plants, recognize single-stranded RNA (ssRNA) in a modular fashion. The maize chloroplast protein PPR10 binds to two similar RNA sequences from the ATPI-ATPH and PSAJ-RPL33 intergenic regions, referred to as ATPH and PSAJ, respectively. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

20
370
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 292 publications
(392 citation statements)
references
References 36 publications
20
370
2
Order By: Relevance
“…All together, the presented data demonstrate that repeats 2, 3, 4 and 5 from our cPPR recognize individual nucleotides and strongly suggest that all repeats within the cPPR are contributing to RNA recognition. These results biochemically validate the computationally predicted code for base recognition as well as previous structural observations 18 , and demonstrate that our engineered cPPRs can bind RNAs in a programmable manner.…”
Section: A Consensus Ppr Protein Scaffoldsupporting
confidence: 69%
See 4 more Smart Citations
“…All together, the presented data demonstrate that repeats 2, 3, 4 and 5 from our cPPR recognize individual nucleotides and strongly suggest that all repeats within the cPPR are contributing to RNA recognition. These results biochemically validate the computationally predicted code for base recognition as well as previous structural observations 18 , and demonstrate that our engineered cPPRs can bind RNAs in a programmable manner.…”
Section: A Consensus Ppr Protein Scaffoldsupporting
confidence: 69%
“…A previous study of PPR10 observed direct hydrogen bonding of adenine, guanine and uracil by S, T and N residues, respectively, at position 4 of the corresponding PPR modules 18 . Specific recognition of cytosine has not previously been observed, although direct hydrogen bonding by N4 was predicted 18 . In our structures, the electrostatic properties highlight the proposed nucleic acid binding groove in the inner face of the superhelix (Fig.…”
Section: A Consensus Ppr Protein Scaffoldmentioning
confidence: 99%
See 3 more Smart Citations